Penguatan Pemberantasan Kejahatan Jalanan dan Aksi Premanisme Tahun 2023: Penguatan Pemberantasan Kejahatan Jalanan dan Aksi Premanisme Tahun 2023 - Saputra, Azis (Jurnal Litbang Polri, 2024)
Increasing development of society gives rise to various social changes which can take the form of changes to norms, regulations and habits. The impacts of social change is emergence of street crime and thuggery which can become a potential threat. Actions of thuggery can be carried out by small groups, as well as large groups. One of the National Police's programs is the eradication of thugs and acts of thuggery which is a follow-up to the National Action Plan. Therefore, Puslitbang Polri needs to conduct research on "Strengthening the Eradication of Street Crime and Actions of Thuggishness" that can be used in making policies. This research uses qualitative and quantitative methods. Respondents consisted of community and staff. The results stated: 1)The most types of street crime and acts of thuggery are theft, robbery, illegal racing and mugging; 2)In 2 out of 10 respondents have been victims of street crime and acts of thuggery; 3)The victims of street crime and acts of thuggery were those with low income levels; 4)Respondents agree that community participation is very necessary to assist in the detection and early warning; 5)Majority respondents agree that police patrols have a significant impact on reducing street crime and thuggery; 6)The community expects the police quickly come in scene of the crime and prosecute the perpetrators of street crimes and thuggery; 7)The partnership between Police and community has an important role in early detection and warning efforts in realizing strengthening the eradication of street crime and acts of thuggery.